The Development of Performance Validity Tests (PVTs) for Indonesia: A Literature Review and Recommendations - Widhi Adhiatma; Marc P. H. Hendriks; Magdalena S. Halim; Roy P. C. Kessels (Buletin Psikologi, 2023)
Neuropsychological tests are proliferating in Indonesia. So far, unfortunately, it is not accompanied by the development of a performance validity test (PVT). According to international neuropsychological standards, using PVTs is essential to determine the validity of the neuropsychological test results. To date, there is no single standardized PVT available in Indonesia. In this article, we describe (1) the concept of performance validity testing, (2) the detection strategy, and (3) the procedure of PVT. Furthermore, several factors which affect PVT failure and its implication on the interpretation of a neuropsychological assessment are discussed. Considering the importance of PVTs incorporation and that it has become a standard by some neuropsychological associations, it is crucial to develop PVTs in Indonesia. Finally, the utilization of PVT should be performed cautiously, as many factors might influence the PVT result.